Farmers may know best - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The spectacular contribution that science has made to agricultural production during the last century-and-a-half has tended to obscure our appreciation of the indigenous knowledge of farming communities. For instance, in the 1940s and 1950s many...